Pendampingan Literasi Keuangan Pada Siswa SDN 2 Abuan, Bangli - Iskandar, Caroline; Haes, Putri Ekaresty (Universitas Negeri Padang, 2023)
Money management is not only a problem for adults who are already working but must be instilled in children from an early age so that they can adopt a frugal lifestyle and can manage their finances from an early age. This community service activity aims to provide an understanding to class VI students at SDN 2 Abuan, Susut District, Bangli Regency about money management and the meaning of a simple and frugal lifestyle. In the implementation of activities, there are three stages, namely the preparation stage, the implementation stage, and the evaluation stage. The material provided in this activity includes setting pocket money, needs, and desires, as well as how to live frugally from an early age. With this activity, class VI students at SDN 2 Abuan, Susut District, Bangli can allocate the pocket money they receive for various needs. In other words, students are able to distinguish precisely the level of importance between needs and wants. Another result of this literacy activity is that students have formed a habit of saving so that at the end of the activity the amount of class VI students' savings increases.